Development of a computer software for optimal design and retrofit of heat exchanger network in a chemical process plant - Ooi, Boon Lee (2005)
Heat-MATRIX, a computer software for heat exchanger network design and retrofit based on the techniques of Pinch Technology and MATRIX (MAximising Total area Reuse In an eXisting process) has been proposed. Heat-MATRIX is a software to utilise the MATRIX technique which has been carefully tailored for use in an existing process plant. The software is a Microsoft Windows-based programme that has been developed to automate, and rapidly as well as efficiently assist the design and retrofit of heat exchanger network. Given a set of candidate process streams with potential for heat exchange, Heat-MATRIX would automatically generate the design targets – i.e. the heat recovery Pinch temperatures, the minimum hot and cold utility targets; both graphically and numerically. In addition, it can also automatically generate the optimal utility combination for a given process, and allow the automatic design of heat exchanger network to achieve the energy targets. Besides that, Heat-MATRIX provides a new tool named Exergy Block Diagram for analysis a retrofit of an existing plant’s heat recovery network. At this stage, the software would automatically generate all probable heat exchange matches and eliminate the infeasible heat transfer matches. In network evolution, Heat-MATRIX also provides a more significant method in terms of cost savings through Path Optimisation. The software would plot a curve of total annual cost versus shifted heat load. From the curve, the software would search for the optimal heat load to be shifted along heat exchanger path.